Strategi Media Relation Impala Network dalam Membangun Brand Awareness - Aditya Jaka Surya Saputra; Rahmawati Zulfiningrum (Departement of Mathematics Education, 2023)
The creative industry has become one of the driving forces of the economy in Indonesia. Impala Network is a company engaged in the creative industry and has a positioning as an aggregator that connects one sector to another. Based on the results of the Impala Network mapping, strategies need to be improved so that people can become more widely acquainted. This study aims to examine Impala Network's media relations strategy in building brand awareness using media relations theory and brand awareness theory. The research uses a qualitative descriptive approach, supported by data collection using in-depth interviews, observation, and documentation. Based on the research results, it can be concluded that the Impala Network has several media relations strategies, namely; 1) Regularly holding quality events to build and establish relationships with several media partners, 2) Using social media platforms such as Instagram & Tiktok to see market trends, 3) Implementing the word of mouth method, 4) Impala Network has a positioning as a creative ecosystem builder (creative aggregator/agency) and one of the Top of mind companies in the creative industry within the coverage area of Semarang City and Central Java Province. Impala Network is currently undergoing a transitional stage from brand recognition to brand recall in order to continue to compete in the national creative industry ecosystem.